Secure Cognitive Radio-Enabled Vehicular Communications under Spectrum-Sharing Constraints - Suneel Yadav; Anshul Pandey; Dinh-Thuan Do; Byung Moo Lee; Adão Silva (Sensors, 2021)
Vehicular communication has been envisioned to support a myriad of essential fifth-generation and beyond use-cases. However, the increasing proliferation of smart and intelligent vehicles has generated a lot of design and infrastructure challenges. Of particular interest are the problems of spectrum scarcity and communication security. Consequently, we considered a cognitive radio-enabled vehicular network framework for accessing additional radio spectrum and exploit physical layer security for secure communications. In particular, we investigated the secrecy performance of a cognitive radio vehicular network, where all the nodes in the network are moving vehicles and the channels between them are modeled as double-Rayleigh fading. Furthermore, adopting an underlay approach, the communication between secondary nodes can be performed by employing two interference constraint strategies at the primary receiver; (1) Strategy I: the secondary transmitter power is constrained by the interference threshold of the primary receiver, and (2) Strategy II: the secondary transmitter power is constrained by both the interference threshold of the primary receiver and the maximum transmit power of the secondary network. Under the considered strategies, we derive the exact secrecy outage probability (SOP) and ergodic secrecy capacity (ESC) expressions over double-Rayleigh fading. Moreover, by analyzing the asymptotic SOP behavior, we show that a full secrecy diversity of 1 can be achieved, when the average channel gain of the main link goes to infinity with a fixed average wiretap channel gain. From the ESC analysis, it is revealed that the ESC follows a scaling law of <semantics>Θ<mfenced separators="" open="(" close=")">ln<mfenced open="(" close=")"><msubsup>Ωm2</msubsup><msubsup>Ωe2</msubsup></mfenced></mfenced></semantics> for large <semantics>Ωm</semantics> and <semantics>Ωe</semantics>, where <semantics>Ωm</semantics> and <semantics>Ωe</semantics> are the average channel gains of the main link and wiretap link. The numerical and simulation results verify our analytical findings.